ANALISIS GALAT BERBAHASA INGGRIS PADA PENULISAN IKLAN LUAR RUANG DI KOTA BANDUNG - Iim Rogayah Danasaputra; Fuji Alamsari (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2018)
This article has aims at analyzing types of outdoors advertising which made errors of English around Bandung City. The method used in the research was descriptive research. The writers collected the data by observing English errors of outdoor advertising around Bandung city, making documentation through capturing photos, then classifying the data based on the types of outdoor advertising and the kinds of English errors done by the advertiser. The results shows that the types of outdoor advertising which made English mistakes were fashion, food and beverage, electronics, general ads, and beautification ads. And then, there were the English errors of outdoors ads found in Bandung City as follows: errors of spelling, word choice, grammar, and word order.